The Dynamics of Farm Land Allocation – Short and Long Run Reactions in a Long Micro Panel - Søren Arnberg; Lars Gårn Hansen (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2010)
This study develops a dynamic multi-output model of farmers' crop allocation decisions that allows estimation of both short-run and long-run adjustments to a wide array of economic incentives. The method can be used to inform decision-makers about a number of issues including agricultural policy reform and environmental regulation. The model allows estimation of dynamic effects relating to price expectations adjustment, investment lags and crop rotation constraints. Estimation is based on micro-panel data from Danish farmers that includes acreage, output and variable input utilisation at the crop level. Results indicate that there are substantial differences between the shortrun and long-run land allocation behaviour of Danish farmers and that there are substantial differences in the time lags associated with different crops. Since similar farming conditions are found in northern Europe and parts of the USA and Canada, this result may have more general interest.
Keywords: C33; Q12; Q15; 330; land allocation; crop rotation; system of dynamic equations; micro panel data; GMM